Peran Media Sosial, Ulasan Daring, dan Kepedulian Lingkungan pada Perilaku Pembelian Green Product - Taufik Fajar Hidayatullah; Yudi Sutarso (At-Tadbir : jurnal ilmiah manajemen, 2023)
This study aims to analyze the role of social media on the marketing of green products by taking the role of online product reviews, subjective norms, environmental concerns, and green purchase intention on green purchase behavior. This study also involves the role of green trust as a moderating variable of the relationship between environmental concern and green purchase intention The data in this study were obtained through a questionnaire of 122 respondents who were used as samples and analyzed through purposive sampling technique. Using two-stage PLS SEM to analyze data, internal model analysis, and external model analysis. The findings in this study indicate that subjective norms have a major role in influencing the purchase intention of environmentally friendly products. Furthermore, online product reviews and social media marketing have a significant role in influencing the green purchase intention The role of green trust is also significant but is not able to moderate the relationship between environmental concern and green purchase intention.